THE PARADOX OF MORAL EDUCATION IN ISLAMIC BOARDING SCHOOLS: THE PHENOMENON OF BULLYING AND ITS IMPLICATIONS FOR THE CHARACTER - Maulana, Muhammad Zaki; BZ, Zakiyah; Rahmatillah, Alda Novita (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Bullying is a significant social issue that occurs in various educational environments, including pesantren. Despite pesantren having strong religious traditions, bullying among students remains a unique challenge. This study highlights the importance of implementing behavioral management as a preventive and corrective measure against bullying. The findings reveal that bullying incidents are primarily verbal and social in nature. The main contributing factors include peer pressure, status gaps, and inadequate supervision. The study demonstrates that behavioral management strategies, such as reinforcing religious values and providing conflict management training, are effective in reducing bullying incidents. This research provides insights into how pesantren can adopt a holistic approach to address bullying, ensuring a safe and supportive environment for all students. Additionally, it emphasizes the role of educational institutions in fostering positive behavior and promoting respect among students. By integrating religious teachings with behavioral management techniques, pesantren can create a conducive atmosphere for the spiritual and social growth of their students, ultimately reducing bullying and enhancing the overall educational experience.